Correlation between Lymphocyte Count and RT-PCR Cycle Threshold Value in Patients with Corona Virus Disease-19 at RS Pelamonia Makassar - Rosdiana Mus; Sasminiarti; Mutmainnah Abbas; Elpira Asmin; Titin Agustina (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: COVID-19 caused by Coronavirus (CoV) attacks the human respiratory system. COVID-19 as an outbreak at the end of 2019 caused deaths all over the world. Diagnosis of COVID-19 through RT-PCR and laboratory test such as lymphocyte was count. Purposes: The aims of the research is the relationship between CT values and lymphocytes. Methods: This type of observational research with a cross sectional study. The sample technique in this study is purposive sampling. The data used is secondary during the July-December 2021 period at the TK II Pelamonia Makassar Hospital. The population in this study was all Covid-19 patients at TK II Pelamonia Makassar Hospital with inclusion criteria of positive RT PCR results, aged 25-50 years and without history of autoimmune disease. The results of lymphocyte and CT values used medical record data. The sample size was 130 subjects accordance theinclussion criteria. Results: The research subjects were 130 subjects consisting of 71 (54.6%) male and 59 (45.4%) female. The mean age of the research was 37.88 years. The average of lymphocyte count is 27.95 and average of CT values is 32.30. Conclusion: There is no relationship between lymphocytes and CT values with gender and there is no significant relationship between CT values with the lymphocytes counts.